Mewujudkan Kota Layak Anak Di Kota Surabaya Melalui Prespektif Collaborative Governance - Amelia, Nadya Salsa; Priambodo, Bayu (Jayapangus Press, 2024)
According to the Minister of State for Women's Empowerment and Child Protection Regulation No. 11 of 2011 concerning development policies for child-friendly districts/cities, child-friendly cities are districts/cities that have a development system based on children's rights through planned integration of commitment and resources of the government, community and the business world. comprehensively and sustainably in policies, programs and activities to ensure the fulfillment of children's rights. One of the cities that implements a child-friendly city policy and has received the highest title in Indonesia is the city of Surabaya, however this is not in accordance with the fact that there are still many acts of violence against children and the number is increasing from year to year. Which can be interpreted as meaning that children's rights have not been fulfilled. The aim of this research is to find out how the Surabaya City Government collaborates with the private sector and the community to create a child-friendly city in the City of Surabaya. This research method uses a descriptive method with a qualitative approach by conducting analysis using the Collaborative Governance method from Ansell and Gash which consists of Starting Conditions, face to face dialogue, trust building, commitment to process, shared understanding, intermediate outcomes, Institutional Design, and Facilitative Leadership. The results of the research show that the collaborative process in realizing a child-friendly city in the City of Surabaya has been carried out and has been quite successful, as evidenced by actors ranging from the Department of Women's Empowerment and Child Protection as well as Population Control and Family Planning in the City of Surabaya, the PLATO Foundation and the Children's Forum The city of Surabaya has carried out collaboration well, even though at the share understanding and institutional design stage between parties there is no specific vision and mission or written memorandum of understanding.